2020
DOI: 10.1002/tox.23047
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanocolloid affects hindbrain vascular formation during medaka embryogenesis

Abstract: Angiogenesis is essential for the normal development of an embryo. Silver nanocolloid (SNC) is known to induce vascular malformation in the medaka embryo. We focused on the development of the central arteries (CtAs) in the hindbrain of Japanese medaka. The CtAs and the basilar artery from which they branch are essential for transporting the blood and nutrients necessary to support the hindbrain parenchyma and the development of the pons and cerebellum from the hindbrain. We exposed medaka embryos at developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…It appears silver, in particular silver NPs, have an inhibitory effect on angiogenesis. These findings were confirmed in multiple studies discussed, presenting substantial in vivo evidence [ [239] , [240] , [241] , [242] , 244 ]. Nevertheless, the in vivo proangiogenic findings should not be overlooked [ 246 ] ( Table 1 and Fig.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…It appears silver, in particular silver NPs, have an inhibitory effect on angiogenesis. These findings were confirmed in multiple studies discussed, presenting substantial in vivo evidence [ [239] , [240] , [241] , [242] , 244 ]. Nevertheless, the in vivo proangiogenic findings should not be overlooked [ 246 ] ( Table 1 and Fig.…”
Section: Discussionsupporting
confidence: 68%
“…Further research investigating molecular mechanisms found silver NPs to inhibit HIF1-α and VEGFR, as well as their proangiogenic target genes [ 240 , 243 ]. In an experiment conducted on medaka fish embryogenesis, the previous antiangiogenic results were corroborated [ 244 ]. Specifically, silver nano-colloid (SNC) was applied to the embryos using epidermal growth factor-like domain 7 (EGFL7) to evaluate angiogenesis.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…We showed that silver can decrease IL-33 expression not only in subcutaneous and abdominal cavity implantation but also in venous patch venoplasty. In humans and mice, IL-33 is mainly produced by endothelial cells, epithelial cells, fibroblast-like cells, and myofibroblasts; IL-33 expression in murine endothelial cells can be induced during inflammation [39]. In this study, decreased IL-33 expression was observed in the silver hydrogel group, partly because silver can inhibit inflammation after patch angioplasty.…”
Section: Discussionmentioning
confidence: 56%
“…In this study, decreased IL-33 expression was observed in the silver hydrogel group, partly because silver can inhibit inflammation after patch angioplasty. In Japanese medaka, silver can induce insufficient angiogenesis and hindbrain vascular formation [40]. Other studies have shown that silver nanoparticles conjugated with heparin derivative possess antiangiogenic properties [41].…”
Section: Discussionmentioning
confidence: 99%